The Mediating Effect of Sleep Quality on the Relationship between PTSD and Physical Activity - Talbot, Lisa S. (American Academy of Sleep Medicine, 2014)
STUDY OBJECTIVES: Physical inactivity is linked to health outcomes such as obesity, diabetes, and psychiatric disorders. Sleep disturbance has been linked to the same adverse outcomes. We examine the influence of sleep on physical activity as a novel approach to understand these relationships. Specifically, our objective was to determine whether low sleep quality predicts low physical activity in posttraumatic stress disorder (PTSD), a disorder associated with sleep disturbance, physical inactivity, and poor health outcomes. METHODS: We used data from the Mind Your Heart Study, a prospective cohort study of 736 outpatients recruited from two Department of Veterans Affairs (VA) medical centers. We assessed PTSD with the Clinician Administered PTSD Scale, sleep quality using an item from the Pittsburgh Sleep Quality Index, and physical activity by self-report at baseline and again one year later. Hierarchical multiple regression models and structural equation modeling were used to examine the relationships among PTSD, sleep, and physical activity. RESULTS: Sleep quality but not PTSD status was prospectively associated with lower physical activity in a model adjusting for age, sex, apnea probability, depression, body mass index, and baseline physical activity (β = 0.129, SE = 0.072, p < 0.01). Structural equation modeling indicated that the results were consistent with sleep quality statistically mediating the relationship between PTSD status at baseline and physical activity one year later. CONCLUSIONS: Worse sleep quality predicts lower physical activity in PTSD, providing possible evidence for a behavioral pathway from disturbed sleep to poor physical health outcomes. CITATION: Talbot LS, Neylan TC, Metzler TJ, Cohen BE. The mediating effect of sleep quality on the relationship between PTSD and physical activity. J Clin Sleep Med 2014;10(7):795-801.